USIA REPRODUKSI TIDAK SEHAT DAN JARAK KEHAMILAN YANG TERLALU DEKAT MENINGKATKAN KEJADIAN ABORTUS DI RUMAH SAKIT TENTARA DOKTER SOEDJONO MAGELANG - Shandra Riestya Prihandini; Wahyu Pujiastuti; Tulus Puji Hastuti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2016)
Abortion is the termination of pregnancy before the fetus is capable of living outside from the womb with gestational age 22 weeks. The dangerous complications of abortion are bleeding, perforation, infection, and shock. In 2013, there are 19 people from 107 cases of abortion who experienced bleeding after abortion. The purpose of this research is to determine the relationship of maternal age and spacing pregnancies with abortion incidence in Army Hospital dr. Soedjono Magelang in 2013.The research type is correlation analytical research with cross sectional time approach. The population is all pregnant women with gestational age 22 weeks who received medical care at maternity ward Army Hospital dr. Soedjono Magelang during 2013 with saturation sampling technique and the sample are 135 respondents. The results showed that abortion is leaning occur in risky age (86,6%) and risky spacing pregnancies (88,6%). The first conclusion, there is significant rela-tionship between maternal age with abortion in RST dr. Soedjono Magelang in 2013 with p value 0.009, r 0,219 mean the closeness of the relationship is weak and the direction is positive so whenever the mother pregnant in the risky age, the probability of the occurence of abortion is bigger. The second conclution, there is significant relationship between spacing pregnancy with abortion in the RST dr. Soedjono Magelang in 2013 with p value 0.006, r 0.232 mean the closeness of the relationship is weak and the direction is positive so whenever the mother pregnant in the risky spacing pregnancies, the probability of the occurence of abortion is bigger. Based on this study expected that midwifes can provide counseling about healthy maternal age and ideal spacing pregnancies and the midwifes are able to take a part in preventing the incident of high-risk pregnancy by an early-detection of risk factors of pregnancy.